Navigating the introduction of anti-amyloid therapy in Europe: a position statement by individual members of the EADC - Frederiksen, Kristian S; Boada, Mercé; Dubois, Bruno; Engelborghs, Sebastiaan; Frisoni, Giovanni B; Georges, Jean; Hort, Jakub; Jönsson, Linus; Kramberger, Milica G; Ousset, Pierre-Jean; Scarmeas, Nikolaos; Schmidt, Reinhold; et al. (Alzheimer's research & therapy, 2025)
INTRODUCTION: Anti-amyloid antibodies for the treatment of Alzheimer ́s disease (AD) are currently being evaluated for approval and reimbursement in Europe. An approval brings opportunities, but also challenges to health care systems across Europe. The objective of this position paper is to provide guidance from experts in the field in terms of navigating implementation. METHODS: Members of the European Alzheimer's Disease Consortium and a representative of Alzheimer Europe convened to formulate recommendations covering key areas related to the possible implementation of anti-amyloid antibodies in AD through online discussions and 2 rounds of online voting with an 80% threshold for a position to be accepted. RESULTS: In total, 24 recommendations were developed covering the research landscape and priorities within research in AD following a possible approval, potential impact on health care systems and diagnostic pathways, and communication to patients about anti-amyloid antibodies. Anti-amyloid antibodies are regarded as a substantial innovation with an important clinical impact. In addition, however, new compounds with other mechanisms of action and/or route of administration are also needed. Approval of new treatments will require changes to existing patient pathways and real-world data needs to be generated. CONCLUSION: Comprehensive guidance is provided on the potential implementation of anti-amyloid antibody therapies in Europe following possible approval. Emphasis is placed on the necessity of regularly updating recommendations as new evidence emerges in the coming years.
Keywords: Alzheimerova nemoc; lidé; Europe; amyloidní beta-protein; Evropa; Amyloid beta-Peptides; Alzheimer Disease; Humans